Novel and emerging treatments for Aicardi-Goutières syndrome. (1st February 2020) - Tonduti, Davide; Fazzi, Elisa; Badolato, Raffaele; Orcesi, Simona
ABSTRACT: Introduction : Aicardi-Goutières syndrome (AGS) is the prototype of the type I interferonopathies, a new heterogeneous group of autoinflammatory disorders in which type I interferon plays a pivotal role. The disease usually manifests itself during infancy, primarily affecting the brain and the skin, and is characterized by cerebrospinal fluid chronic lymphocytosis and raised levels of interferon-alpha and by cardinal neuroradiological features: cerebral calcification, leukoencephalopathy and cerebral atrophy. Recently many aspects of the pathogenesis of AGS have been clarified, making it possible to hypothesize new therapeutic strategies. Areas covered : We here review recent data concerning pathogenesis and novel therapeutic strategies in AGS, including the use of Janus kinase inhibitors, reverse transcriptase inhibitors, anti-IFN-α antibodies, anti-interleukin antibodies, antimalarial drugs and other cGAS inhibitors. Expert opinion : Thanks to the identification of the molecular basis of AGS, many aspects of its pathogenesis have been clarified, making it possible to propose new therapeutic strategies for AGS and type I interferonopathies. A number of therapeutic options are now becoming possible, even though their efficacy is still to be proven. However, in spite of research advances coming from clinical trials and case series, there are still a number of open questions, which urgently need to be addressed.